Quantification of proteinuria in mild preeclampsia with random albumin creatinine ratio - Aziz, Ahmad; Elshahawy, Yasser; Sany, Dawlat; El Mandooh, Mohamed (African Journal of Nephrology, 2010)
<p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Objective: To investigate the whether spot urinealbumin/creatinine ratio (ACR) compared to the 24hurinary protein (gold standard) to detect significantproteinuria in patients with preeclampsia. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Study design:80 pregnant patients diagnosed to have hypertension inlate pregnancy were instructed to collect urine during a24-hour period. Albumin creatinine ratio was evaluatedin a random urinary specimen and morning samples forquantization of proteinuria. Out of these, 78 patientsfulfilled the inclusion criteria. The predictive value of therandom urinary ACR for the diagnosis of significantproteinuria was estimated by using various cutoff valuesof urinary ACR in comparison to 24-h urine collection asthe gold standard. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Results: 70 (89%) patients had preeclampsia. The meanmorning systolic blood pressure on the day of the urinecollections was 150 mmHg and mean diastolic bloodpressure 114 mmHg. The mean total protein was1961.46+1683.02 mg/24h, and the urinary ACR inrandom samples was 781.31+1041 mg/g creatinine,while in the morning sample urinary ACR was886.43+1180.9 mg/g creatinine. There was a statisticallysignificant positive correlation between in 24-hours urineproteins and ACR in both daytime and morning urinesamples. The best cutoff point for ACR in randomsample was 262.5 mg /g creatinine as with a sensitivityof 85.5% and a specificity of 81.8%, the positivepredictive value was 96.7% and negative predictive valuewas 47.4%. While the best cutoff point for ACR inmorning sample was 240 mg /g creatinine with asensitivity of 94.2% and a specificity of 63.6%, thepositive predictive value was 94.2% and negativepredictive value was 63.6%. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Conclusion: Albumin/creatinine ratio is not an ideal diagnostic test to replace 24-hour urine collection for the diagnosis of preeclampsia. However, it can be used as a screening test with sensitivity 94% when the cut point of albumin/creatinine ratio of the morning urine sample is set below 240 mg/g creatinine.